ILLEGAL CROSS-BORDER TRADE OF PROTECTED SPECIES OF WILD FAUNA AND FLORA - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
It is estimated that the international trade in wild plants and animals annually worth several billion dollars, hundreds of millions of species are traded: live specimens of animals and plants and products derived from them, including food products, exotic leather products, wooden musical instruments, timber, souvenirs, drugs, cosmetics and more. Proportion of exploitation of certain plant and animal species are large, so that their traffic together with other factors, such as habitat loss, greatly endangering their populations driving some species to extinction. Although certain species of wild animals and plants are not endangered by trade, traffic regulation is necessary to ensure that trade that meets the requirements of sustainable development in order to preserve the natural resources for the future, and in particular to prevent the damaging effects of illegal trade in protected species in cross-border context.